2021
DOI: 10.3389/fnbeh.2020.618180
|View full text |Cite
|
Sign up to set email alerts
|

PsyCoP – A Platform for Systematic Semi-Automated Behavioral and Cognitive Profiling Reveals Gene and Environment Dependent Impairments of Tcf4 Transgenic Mice Subjected to Social Defeat

Abstract: Recently, hundreds of risk genes associated with psychiatric disorders have been identified. These are thought to interact with environmental stress factors in precipitating pathological behaviors. However, the individual phenotypes resulting from specific genotype by environment (G×E) interactions remain to be determined. Toward a more systematic approach, we developed a novel standardized and partially automatized platform for systematic behavioral and cognitive profiling (PsyCoP). Here, we assessed the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 58 publications
(38 reference statements)
2
18
0
Order By: Relevance
“…The PsyCoP test battery consists of a diverse panel of well-established behavioral tests and most of the procedures are at least partially automated to minimize the influence of the experimenter. In this and previous studies 17 , 18 , we found impairments in cognitive flexibility and fear memory in the Tcf4 tg x SD ( Tcf4 SD) GxE mouse model, making it particularly suited to study aspects of cognitive symptoms of schizophrenia spectrum disorders in pharmacological validation experiments. Although the genetics of psychiatric disorder endophenotypes were found to be complex, modeling selected endophenotypes based on conserved neurobiological systems is thought to yield higher construct validity than trying to model complex neuropsychiatric disorders in mice 19 , 20 .…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…The PsyCoP test battery consists of a diverse panel of well-established behavioral tests and most of the procedures are at least partially automated to minimize the influence of the experimenter. In this and previous studies 17 , 18 , we found impairments in cognitive flexibility and fear memory in the Tcf4 tg x SD ( Tcf4 SD) GxE mouse model, making it particularly suited to study aspects of cognitive symptoms of schizophrenia spectrum disorders in pharmacological validation experiments. Although the genetics of psychiatric disorder endophenotypes were found to be complex, modeling selected endophenotypes based on conserved neurobiological systems is thought to yield higher construct validity than trying to model complex neuropsychiatric disorders in mice 19 , 20 .…”
Section: Introductionsupporting
confidence: 61%
“…In this study, we used the previously established profiling platform PsyCoP to assess the effect of spironolactone, particularly on the cognitive performance in the Tcf4 SD ‘2-hit’ mouse model 17 . We treated the mice either with aripiprazole alone or in combination with spironolactone as an add-on treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal models of gain and loss of function of Tcf4 have shown its relevance for cognition, sensorimotor gating and neuroplasticity [68]. In addition, gene x psychosocial stress interactions have been reported for Tcf4 [69], but little is known about relevant molecular pathways and brain regions for this interaction. With DiffBrainNet we showed that Tcf4 mediates GCs effects in two sub-regions of the hippocampal formation, ventral and dorsal DG, at the gene- and at the network-levels since it is DE in those but only at the network-level for the PFC where is not a DE gene.…”
Section: Discussionmentioning
confidence: 99%